Hak Asuh Anak Akibat Perceraian (Studi Perkara Nomor 0679/Pdt.G/2014/PA TnK) - Meita Djohan Djohan (Law Faculty of Universitas Bandar Lampung, 2016)
Marriage is an attempt to unite different persons from each other. In fact, no one who wants marriage ended in a divorce. With the breakdown of a marriage will be legal consequences that follow, one of which is the Custody over children born of the marriage. The problems of this study, how the custody of children after divorce ?. Juridical approach Normative and Empirical, type of data is secondary data and primary data. The data collection and Library Studies Field Studies were then analyzed qualitatively. Results of the study can be argued that, Custody child is when seen in terms of normative, children who are under 12 years old is the custody of his mother, but based on the jurisprudence of the Supreme Court of the Republic of Indonesia Number 110 K / AG / 007 dated 7 December 2007 that in principle stated that the maintenance of the child, not merely of those most entitled, but to see and put forward is the best interests of the child. Suggestions deliberation should be done if there is a dispute on the division of custody of the child but if there is no way out is better to use the courts.